Amplification rationale for hearing aids based on characteristics of the Japanese language. Issue 1 (February 2022) - Shiraishi, Kimio; Wada, Makiko; Christiansen, Thomas Ulrich; Behrens, Thomas
Abstract: Objective: Hearing aid amplification rationales have typically been developed by using global averages of the long-term average speech spectrum (LTASS) from Western European languages. However, there are few reports on hearing-aid amplification based on acoustic-phonetic characteristics of the Japanese language. This study's objective is to investigate the LTASS for Japanese, and to compare a typical amplification rationale originally developed mainly for Western European languages with an amplification rationale specifically adjusted to the LTASS for Japanese. Methods: LTASS for two speech materials provided by four Japanese talkers were analyzed using 1/3 octave bandwidth filters. The speech was recorded with different levels of vocal effort, yielding three LTASS for "soft", "moderate" and "loud" speech. From these results, a gain offset of the hearing-aid amplification for Japanese was obtained as compared to ANSI S3.5. Speech intelligibility for an amplification rationale for Western European languages and the newly-developed Japanese version was obtained for presentation levels of 50 dB SPL, 65 dB SPL and 80 dB SPL. Nineteen people with mild to moderate hearing loss participated in the speech intelligibility experiment. Scores in% correct were arcsine-transformed and subjected to repeated measures ANOVA with pairwise comparisons of significant main effects using Bonferroni adjustments for multiple comparisons. Results: The LTASS for Japanese was slightly different from the values of previous reports. A comparison of LTASS values to ANSI S3.5 with values for Japanese showed that the Japanese amplification rationale for "moderate" speech levels required more gain in the low-frequency area, and less gain in the high-frequency area. There was no significant difference in the speech intelligibility level between the amplification characteristics of Western European languages and Japanese language at each presentation level. Conclusion: It was shown that for hearing-aid amplification for Japanese, adjustments based on LTASS differences for Western European Languages could be made. This preserved speech intelligibility at the same level as the original amplification rationale, suggesting that there was no need to consider differences in phonetics of Japanese to optimize speech understanding.